التفاؤل الرياضي والطلاقة النفسية وعلاقتهما بدافعية الإنجاز الرياضي للاعبي كرة السلة - الحيالي، علي عبدالإله يونس; السعدون، أحمد حسين جاسم; الزبيدي، محمد خالد محمد داؤد (جامعة تكريت - كلية التربية البدنية وعلوم الرياضة, 2017)
تهدف هذه الدراسة إلى: - التعرف على المتغيرات النفسية (التفاؤل الرياضي والطلاقة النفسية ودافعية الإنجاز الرياضي) للاعبي منتخبات جامعات العراق للمنطقة الشمالية بكرة السلة. - التعرف على العلاقة بين المتغيرات النفسية التفاؤل الرياضي والطلاقة النفسية) بدافعية الإنجاز الرياضي للاعبي منتخبات جامعات العراق للمنطقة الشمالية بكرة السلة. استخدم الباحثون المنهج الوصفي لملائمة وطبيعة مشكلة البحث، واشتمل مجتمع البحث على لاعبي منتخبات الجامعات العراقية (للمنطقة الشمالية) بكرة السلة والمتمثلة (الموصل، تكريت، ديالي، الأنبار، كركوك، سامراء، الحدباء الأهلية) والبالغ عددهم (70) لاعبا، للعام الدراسي (2013-2014)، أما عينة البحث فقد تكونت من (60) لاعبا، يمثلون نسبة (85.71%) من مجتمع البحث الأصلي، وقد استخدم الباحثون الوسائل الإحصائية (الوسط الحسابي الانحراف المعياري، قانون النسبة المئوية، قانون المتوسط الفرضي، اختبار (ت) لعينة واحدة، معامل الارتباط البسيط (بيرسون)، معادلة سبيرمان- براون، تحليل التباين اختبار دنكن) واستنتج الباحثون ما يأتي:- بان عينة البحث تمتلك درجات جيدة من المتغيرات النفسية (التفاؤل الرياضي، الطلاقة النفسية، دافعية الإنجاز الرياضي) من خلال مقارنة قيم الأوساط الحسابية مع قيم المتوسطات الفرضية للمقاييس المطبقة في البحث الحالي. This study aims to: -To identify the psychological variables (optimism Sports and fluency psychological and athletic achievement motivation) for basketball players. -Understand the relationship between psychological variables (optimism mathematical fluency psychological) Bdafieh sporting achievement for basketball players. The researchers used a descriptive approach to fit the nature of the research problem, and included the research community on the players, teams of Iraqi universities (for the Northern District) basketball and of (Mosul, Tikrit, Diyala, Anbar, Kirkuk, Samarra, humpback civil) totaling (70) players, for the academic year (2013-2014), the research sample consisted of (60) players, representing the percentage (85,71 %) of the original research, researchers have used statistical methods (mean, standard deviation, the law of the percentage, the average law hypothesis, t-test for one sample, simple correlation coefficient (Pearson), the equation of Spearman- Brown, analysis of variance.)The researchers concluded Mayati: that the sample has good grades of psychological variables (optimism Sports and fluency psychological and achievement motivation) by comparing the values of the media calculations with the values of averages premise of the standards applied in the current research, as well as the emergence of significant relationship between psychological variables (optimism Sports and fluency psychological and achievement motivation) Bdafieh sporting achievement for basketball players.
Keywords: علم النفس الرياضي -- التفاؤل الرياضي -- الطلاقة النفسية -- الإنجاز الرياضي -- لاعبو كرة السلة